Effect of body lipid content is linked to nutritional adaptation in the acclimation responses of mesic-adapted Paederus to seasonal variations in desiccation stress. (May 2021) - Bong, Lee-Jin; Wang, Chia-Yu; Shiodera, Satomi; Haraguchi, Takashi F.; Itoh, Masayuki; Neoh, Kok-Boon
Graphical abstract: Highlights: Desiccation stress causes mesic-adapted Paederus to lose body water content. Cuticular permeability might play a minor role in reducing excessive water loss. Sugars in hemolymph did not play a central role in enhancing insect water budget. Increased internal metabolic water was mediated by lipid catabolism. Lipids were accumulated through dietary shifts from herbivore prey to plants. Abstract: Desiccation stress causes mesic-adapted arthropods to lose their body water content. However, mesic-adapted Paederus beetles can survive over prolonged periods under dry field conditions, suggesting that these beetles adopt an array of water conservation mechanisms. We investigated the water balance mechanisms of field-collected Paederus adults over a 14-month sampling period. We also assessed their nutritional adaptations by performing a stable isotope analysis to examine their diet. The water loss rate (WLR) of the beetles was significantly associated with the rice crop cycle and saturation deficit. The cuticular permeability (CP) of adult beetles was maintained at < 30 µg cm −2 h −1 mmHg −1 ; however, CP increased significantly with the WLR. This result indicates that CP might play a minor role in reducing excessive water loss in beetles. The beetles' body water content and percentage total body water content increased when the WLR was high. Trehalose, glucose, and glycogen did not appear to play a central role in enhancing the water reserves in the insects. The body lipid content ranged from 0.22 ± 0.06 to 0.87 ± 0.07 mg and was negatively associated with the WLR. This association indicates that the increase in internal metabolic water was mediated by lipid catabolism. Stable isotope analysis results revealed that the Paederus beetles shifted their diet to carbohydrate-rich plants when the saturation deficit increased and the associated WLR reached its peak; otherwise, they consumed a high amount of staple carbohydrate-poor herbivore prey. The accumulation of energy reserves in the form of lipids through seasonal dietary shifts may exert major effects on the survival and population success of mesic-adapted Paederus beetles.